Solid-State Metathetic Synthesis of Ag-ZnWO4/Zeolite-A: A Porous Composites Assisted by Microwave Irradiation - Lim, C.S. (Asian Journal of Chemistry, 2011)
Ag-ZnWO4/zeolite-A porous composites were successfully synthesized from solid-state metathetic method using microwave irradiation. The wolframite-type ZnWO4 has been synthesized where the characteristics of solid-state metathetic reaction and the formation of high lattice energy by-product NaCl drives the reaction toward completion. The Ag-ZnWO4/zeolite-A porous composites were entirely completed at 600 ºC. The monoclinic-like crystals of ZnWO4 are primarily co-mixed with porous zeolite-A. The spherical small particles of silver are well immobilized in the porous ZnWO4/zeolite-A matrix.